Antitubercular metabolites from the marine-derived fungus strain Aspergillus fumigatus MF029. Issue 16 (12th August 2021) - Song, Zhijun; Liu, Yu; Gao, Jieyu; Hu, Jiansen; He, Hongtao; Dai, Shengwang; Wang, Luoqiang; Dai, Huanqin; Zhang, Lixin; Song, Fuhang
Abstract: During the systematic screening of bioactive compounds from our marine natural product library, crude extract of the marine-derived fungus strain Aspergillus fumigatus MF029 exhibited moderate bioactivities against Bacillus subtilis, S taphylococcus aureus, methicillin-resistant S. aureus, and Mycobacterium bovis bacillus Calmette–Guérin (BCG). Further chemical investigation resulted in the identification of two new compounds, chaetominine A (1 ) and sphingofungin I (2 ), together with four known compounds, emodin (3 ), chaetominine (4 ), sphingofungin D (5 ) and trypacidin (6 ). Trypacidin displayed potential antitubercular activity with MIC value of 1.25 μg/mL. Graphical Abstract: